2023
DOI: 10.1097/rlu.0000000000004565
|View full text |Cite
|
Sign up to set email alerts
|

A Discordant Pattern of Uptake on 68Ga-PSMA PET/CT Versus 18F-Fluciclovine PET/CT in Radiation-Induced Hepatitis

Abstract: A 62-year-old woman with right-sided invasive lobular breast carcinoma completed external beam radiotherapy 6 weeks before undergoing a 68Ga-PSMA PET/CT and 18F-fluciclovine PET/CT scan as part of an ongoing clinical trial (NCT04750473) assessing the performance of these molecular imaging modalities in invasive lobular breast carcinoma. The 68Ga-PSMA PET/CT demonstrated a band-like area of increased radiotracer uptake in the dome of the right lobe of the liver anteriorly, whereas 18F-fluciclovine PET/CT done a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(14 reference statements)
1
4
0
Order By: Relevance
“…However, reports of increased PSMA uptake due to hepatitis are rare. In a case report published by Adediran et al increased uptake on Ga68-PSMA PET/CT due to radiation hepatitis in the liver dome after radiotherapy in a patient diagnosed with invasive lobular carcinoma of the right breast (27). In our study, one patient with false positive liver uptake had histopathological con rmed cholestatic hepatitis.…”
Section: Discussionsupporting
confidence: 60%
“…However, reports of increased PSMA uptake due to hepatitis are rare. In a case report published by Adediran et al increased uptake on Ga68-PSMA PET/CT due to radiation hepatitis in the liver dome after radiotherapy in a patient diagnosed with invasive lobular carcinoma of the right breast (27). In our study, one patient with false positive liver uptake had histopathological con rmed cholestatic hepatitis.…”
Section: Discussionsupporting
confidence: 60%
“…Only 1 other case to of probable radiation-induced hepatic injury demonstrating PSMA activity has been reported. 13 Multiple studies have shown significant FDG uptake in radiation-induced liver injury, attributed to heightened glucose uptake by leukocytes in the inflammatory process. Recently newer tracers such as 18 F-FAPI and now PSMA have been shown to demonstrate increased uptake with concurrent absent or normal FDG uptake in radiation-induced liver injury.…”
mentioning
confidence: 99%
“…The discordance between PSMA and FDG uptake in the affected liver region is of interest, possibly indicating PSMA expression in the chronic phase of fibrotic tissue remodeling. Only 1 other case to of probable radiation-induced hepatic injury demonstrating PSMA activity has been reported 13 . Multiple studies have shown significant FDG uptake in radiation-induced liver injury, attributed to heightened glucose uptake by leukocytes in the inflammatory process.…”
mentioning
confidence: 99%
“…Avidity on PSMA-targeted PET imaging has been widely reported in multiple nonprostate neoplastic and nonneoplastic conditions, including cancer therapy-related injuries. [1][2][3] Prostate-specific membrane antigen avidity due to aberrant vascular anatomy has not been widely reported. This case highlights many important lessons, including the consistency of this artifactual uptake with different PSMA-targeting radiopharmaceuticals and across different imaging techniques.…”
mentioning
confidence: 99%
“…The coronal postcontrast T1FS sequence ( D ) demonstrates the aberrant vessel arising from the duodenum/pancreatic head and terminating within hepatic segment IV ( D , arrows). Avidity on PSMA-targeted PET imaging has been widely reported in multiple nonprostate neoplastic and nonneoplastic conditions, including cancer therapy–related injuries 1–3 . Prostate-specific membrane antigen avidity due to aberrant vascular anatomy has not been widely reported.…”
mentioning
confidence: 99%